Acute Midgut Volvulus in a Previously Healthy 9- Year Boy - issa, kumait; Ali, Wajeeh (Iranian Journal of Pediatric Surgery, 2021)
Intestinal malrotation is an uncommon cause of bowel obstruction after the first month of life. Nevertheless, this abnormality can be diagnosed even at older ages. In this case, we present a 9-year-old, healthy, well-nourished boy who came in Emergency Department with intermittent cramping abdominal pain, associated with bilious vomiting. After clinical examination, plain AXR, and ultrasonography with no important findings, we performed doppler ultrasound screening of the abdominal vessels, in which abnormal orientation of superior mesenteric vessels was found. After that, contrast-enhanced CT scan was performed, which confirmed the diagnosis of intestinal malrotation, and revealed the "Whirlpool Sign", confirming the diagnosis of midgut volvulus. He underwent laparotomy and Ladd´s procedure was done for him. We recommend investigation for the possibility of intestinal malrotation in all patients of non-specific abdominal pain regardless of age, even if there is no intestinal obstruction.